Digital technologies that change pharmacy practice - key benefits and challenges - Odalović, Marina (Archives of Pharmacy, 2022)
The WHO defines eHealth as the use of information and communication technologies (ICT) for health, e.g. treating patients, research, educating the health workforce, tracking diseases and monitoring public health”. eHealth covers the interaction between patients and health-service providers, institution-to-institution transmission of data, or peer-to-peer communication between health professionals. Under the term e-health, the terms m-health (use of mobile ICT devices for health purposes) and telehealth (use of telecommunication technologies for health purposes) also appear. The pharmacy is developing in the fields of e-pharmacy and telepharmacy. Many pharmacists use eHealth tools on a daily basis, whether it is dispensing electronic prescriptions, checking for medication interactions, providing support for adherence etc. Community pharmacists acknowledge the potential of Big Data and Artificial Intelligence (AI) for European health systems and consider these technologies as a useful tool to support healthcare professionals. However, in daily practice at national level, these tools shall be always accompanied by pharmacists’ expert and professional advice, in order to improve therapy effectiveness and offering the highest standard of pharmacy services to its patients. The trend of digitalization, including the digital economy has accelerated the pace at which new technologies are transforming the healthcare sector. Adaptation of national regulations to the use of ICT for the purpose of patient health care, as well as harmonization with European regulations in this area is recognized as one of the future challenges that need to be successfully overcome on the way to even safer and more efficient pharmaceutical health care in pharmacies.